Entre ausências e emergências: uma extensão rural pública ou privada? - Alves, Nára Beatriz Chaves (2018)
The services of technical assistance and rural extension (Ater), are configured in Brazil as an important public policy in countryside, non-formal and educational environment destined, among others, to family farmers. Ater services are offered through public organizations (official representation) and private organizations. There are several civil society actors, in a greater or lesser extent, providing Ater services in Brazil. Otherwise, some agendas of research (OLINGER, 1996) also point out the low investment in capacity of governments with the allocation of insufficient resources to the demand demanded by the beneficiaries of Ater services. Therefore, the present thesis, “Between absences and emergencies: a public or private rural extension?”, seeks to understand how absences and emergencies modify the nature of the Technical Assistance and Rural Extension service (Ater), after the Brazilian State reform in the decade 1990, with the implementation of public services in contrysides through the sharing of public services to private entities, namely, the Ater services.The approach of the study was descriptive with a qualitative methodology, through the symbolic cartography of the Ater services of the city of Torres, RS, using different proceedings and different sources of data, such as direct observation, research in records, analysis of relevant legislation, study of documents of the entities involved and conducting semester interviews, through the representatives of public and private organizations. It stands out among the results found are that the State does not implement Ater services, only coordinates and formulates rural development policies. There is a designation of the services to the service providers, through the official representation entity of the services and private and non-profit entities. Ater services are perceived as necessary to the beneficiaries, but the way it is conducted, there is the displacement of boundaries between public and private, once as the Ater services are performed in large proportion by civil associations if we observe, beginning with the gradual changes in public services intensified by the reform of the State apparatus (1995),the Ater services incorporate the determinations and guidelines of the public administration, and consequently, of the national agricultural and agrarian policy guidelines and with that (re) configured the services.